2020
DOI: 10.3390/microorganisms8050763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Highly Efficient DNA Extraction Method for Bacillus anthracis Endospores

Abstract: A variety of methods have been established in order to optimize the accessibility of DNA originating from Bacillus anthracis cells and endospores to facilitate highly sensitive molecular diagnostics. However, most endospore lysis techniques have not been evaluated in respect to their quantitative proficiencies. Here, we started by systematically assessing the efficiencies of 20 DNA extraction kits for vegetative B. anthracis cells. Of these, the Epicentre MasterPure kit gave the best DNA yields and quality sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…A bacterial colony grown on blood agar was chemically inactivated and DNA isolated using the MasterPure™ Gram Positive DNA Purification kit (Lucigen, Middleton, WI, USA) as described for Gram-positive bacteria, with minor modifications as described in [ 19 ]. DNA concentrations were quantified using the Qubit dsDNA HS Assay Kit (Thermo Fisher Scientific, Dreieich, Germany), according to the supplier’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…A bacterial colony grown on blood agar was chemically inactivated and DNA isolated using the MasterPure™ Gram Positive DNA Purification kit (Lucigen, Middleton, WI, USA) as described for Gram-positive bacteria, with minor modifications as described in [ 19 ]. DNA concentrations were quantified using the Qubit dsDNA HS Assay Kit (Thermo Fisher Scientific, Dreieich, Germany), according to the supplier’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…For B. anthracis, previous studies have demonstrated that a 100% efficient DNA isolation from the purified spores is not achievable (Knüpfer et al . 2020). Thus, for quantifying the target cells used for LOD‐determination, we relied on the ddPCR results for Y. pestis and F. tularensis and microscopic counting results for B. anthracis .…”
Section: Resultsmentioning
confidence: 99%
“…Since quantitative DNA extraction from B. anthracis spores is very difficult even using optimized DNA isolation procedures (Knüpfer et al . 2020), spore concentration was quantified by microscopic counting and by plating on LB‐Agar. For each organism, quantified samples were serially diluted in 1 : 10 steps before application to LFA, with Y. pestis and F. tularensis diluted in a 0·9% NaCl solution, and B. anthracis spores diluted in sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the only hitherto existing rtPCR targeting the 16S rRNA gene of Y. pestis failed to discriminate between Y. pestis and other bacteria of the genus Yersinia (Tomaso et al, 2003). For F. tularensis, a rtPCR successfully targeting the 16S rDNA has been described (Knüpfer et al, 2020). However, in its present form, the sensitivity of this assay is about 86 colony forming units (CFU)/ml (Knüpfer et al, 2020) and thus not optimal.…”
Section: Introductionmentioning
confidence: 97%
“…For F. tularensis, a rtPCR successfully targeting the 16S rDNA has been described (Knüpfer et al, 2020). However, in its present form, the sensitivity of this assay is about 86 colony forming units (CFU)/ml (Knüpfer et al, 2020) and thus not optimal.…”
Section: Introductionmentioning
confidence: 99%